Belarus and Kazakhstan: comparative analysis of socio-economic development - Gospodarik, Catherine G.; Kisselev, Andrei V. (Journal of the Belarusian State University. Economics, 2023)
The authors of the article analyse the experience of economic development of the EAEU partners Belarus and Kazakhstan over 30 years (1992–2022). The dynamics of economic growth and an increase in the share in the world economy are given. Considerable attention is paid to financial development and the formation of the investment process and capital markets of these countries. The state’s efforts to improve the efficiency of innovation systems are analysed. Recommendations on mutual borrowing of transformational experience are given.
Keywords: two-coordinate model; investment process; financial development; EAEU; export quota; mutual trade; economic growth; foreign trade; trade flows